Perception of Students' Evaluation of Teaching Performance by Lecturers in Afe Babalola University, Ado-Ekiti, Nigeria - Funmilayo Yemi Ojo (ABUAD Journal of the Humanities-AGIDIGBO)
The use of student evaluation of teaching effectiveness to assess lecturers' performance in the classroom is one of the common and most controversial practices in tertiary institutions all over the world. The need for improvement in undergraduate teaching performance necessitated continuous research of this subject. The sample included 100 respondents drawn from lecturers attending a workshop on "Improved Teaching and Learning Methods" organized in a private university in Ekiti. Data were collected from lecturers by means of the questionnaire developed by the researcher. t-test analysis was used to analyze the data for the two hypotheses tested. Results indicated no significant difference between male and female lecturers perception of students' assessment of lecturers teaching effectiveness. Responses of both senior and junior lecturers were also positive. It is therefore recommended that student evaluation oflecturers' performance should be made mandatory and conducted regularly in Nigerian universities